Philosophy as a Way of Life: Uncommon Schooling and the Prospect for the Humanities (Nóema, 2023)
This paper tries to reclaim the idea of philosophy as a way of life – an idea and a name associated especially with Pierre Hadot. This involves the reconsideration of the task of philosophy and of its practicality. Philosophy faces a crisis of identity. On the one hand, in the tide of the global economy, the division between useful and useless knowledge has been reinforced, and philosophy tends to be categorized as the latter. On the other hand, philosophy has in some quarters become assimilated into the trend of self-improvement – in Japanese, Jiko Keihatsu, an idea that carries the distinctive connotation of enlightenment of oneself, which is fairly close to the idea of self-help in the U.S.A and in Europe. In this trend, «fast knowledge» is treasured and the language of philosophy is translated into easy, accessible terms. Torn between these two tendencies, philosophy needs to reconsider its use, neither turning its «uselessness» into something to be proud of, as has sometimes been the tendency in the liberal arts tradition, nor selling out to «usefulness» under the pressures of the global economy; it needs to reaffirm its intrinsic value. In this paper, I shall point to the idea of philosophy with a higher sense of use and with an alternative economy of education, one that necessitates the conversion of the way we see ourselves, others and the world.
Keywords: Philosophy as a way of life; jiko keihatsu; uncommon schools; philosophy as the education of the grownups; Cavell; Thoreau